2022
DOI: 10.1021/acs.jchemed.1c01130
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Learning of Ionic Organic Reactions in Organic Chemistry Based on Acid–Base Theory

Abstract: Organic chemistry is the study of organic compounds containing hydrocarbons and their derivatives. It is similar to inorganic chemistry in terms of the cognitive model. However, the vast number of organic compounds has added to the difficulty in learning organic chemistry with compressed class hours in engineering majors. The integration of the process learning and reinforcement theories and organic chemistry content has led to a new notion, i.e., understanding and learning organic compounds with different fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The shift from quantitative to qualitative problem-solving skills has been attributed to the long-standing sentiment that organic chemistry is the gatekeeper course for students (Garg, 2019;Arnaud, 2020). In the past decade, the number of organic chemistry education research articles has significantly grown, with mechanistic problem-solving being a central focus, as well as the role of acid-base concepts in rationalizing organic reactions (Graulich, 2015;Schmidt-McCormack et al, 2019;Petterson et al, 2020;Salame et al, 2020;Gao et al, 2022;Yue and Gu, 2022;Boothe et al, 2023). Two studies analyzed expert responses to gauge the significance of acid-base chemistry in organic reactions.…”
Section: Acid-base Chemistry In Organic Chemistry Problem Solvingmentioning
confidence: 99%
“…The shift from quantitative to qualitative problem-solving skills has been attributed to the long-standing sentiment that organic chemistry is the gatekeeper course for students (Garg, 2019;Arnaud, 2020). In the past decade, the number of organic chemistry education research articles has significantly grown, with mechanistic problem-solving being a central focus, as well as the role of acid-base concepts in rationalizing organic reactions (Graulich, 2015;Schmidt-McCormack et al, 2019;Petterson et al, 2020;Salame et al, 2020;Gao et al, 2022;Yue and Gu, 2022;Boothe et al, 2023). Two studies analyzed expert responses to gauge the significance of acid-base chemistry in organic reactions.…”
Section: Acid-base Chemistry In Organic Chemistry Problem Solvingmentioning
confidence: 99%
“…Yue and Gu suggested a simpler analogy by further developing the learning logic of inorganic chemistry into the transfer of organic chemistry mechanisms. They emphasized organic functional group reactions from the perspective of acid–base theory and restructured the knowledge of organic chemistry to enhance student learning efficiency . Additionally, some researchers have proposed using legends, cartoons, games, and other methods to classify and summarize reactions, thereby replacing fragmented learning methods with systematic connections and reducing the tedium associated with organic chemical reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized organic functional group reactions from the perspective of acid−base theory and restructured the knowledge of organic chemistry to enhance student learning efficiency. 8 Additionally, some researchers have proposed using legends, 9 cartoons, 10 games, 11 and other methods 12−14 systematic connections and reducing the tedium associated with organic chemical reaction mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While student understanding of acid-base reactions in general chemistry has been highly studied (Cooper et al, 2016;Drechsler & Van Driel, 2008;Kala et al, 2013;Nakhleh, 1994;Nakhleh & Krajcik, 1994;Nyachwaya, 2016;Romine et al, 2016;Sheppard, 2006), work to identify alternative conceptions of acid-base reactions in organic chemistry students has been less prevalent. Nevertheless, the role of acid-base reactions in organic chemistry is gaining traction in the literature (Graulich, 2015;Petterson et al, 2020;Salame et al, 2020;Schmidt-McCormack et al, 2019;Yue & Gu, 2022). Alison Flynn's research group analyzed twenty-eight reactions routinely taught in organic chemistry or biochemistry courses and identified that 85% of such reactions required a Brønsted acid-base step in the mechanism, either for nucleophile or electrophile formation or in the workup (Stoyanovich et al, 2015).…”
Section: Introductionmentioning
confidence: 99%